Palestine-Israel and the Neoliberal Ideal: Comments (American Journal of Islam and Society, 2017)
When I was asked to review this piece for AJISS, I was excited to see scholarlywork relating the Palestinian-Israeli conflict to neoliberalism. Reading thepaper only heightened my enthusiasm; by invoking neoliberalism the authoradds new insights into the nature of this conflict and why it persists.More often than not, we try to understand this conflict in terms of nationalismor religion. Thus framing it as a clash of intractable ideologies,which allows us to blame it on some uncompromising Islamic extremistsand Zionist settlers, has become convenient – although neither is representativeof the majority of either the Palestinians or the Israelis.Given this approach, we in the West have a tendency to look upon Israelisand/or Palestinians as the cause of their own problem. We scratchour heads when they do not come to an agreement, throw up our handswhen the next president’s peace plan fails, and figure that those people arejust that way – always have been and always will be. Not only is this viewpointintellectually weak, but it is politically damaging because it ignoresthe true causes of the conflict and justifies indifference to violations ofhuman rights.